2015
DOI: 10.1002/app.42552
|View full text |Cite
|
Sign up to set email alerts
|

Neural network modeling of the preparation process of a siloxane‐organic polyazomethine

Abstract: Although apparently simple, the polycondensation reaction leading to polyazomethine is difficult to control because of its equilibrium character, the conversion degree being influenced by a series of parameters. The reaction between a siloxanediamine, 1,3bis(3-aminopropyl)tetramethyldisiloxane, and terephthalaldehyde was performed here in solution (in tetrahydrofuran) without byproducts removal and in absence of any catalyst or pH modifier. Different conditions (co-monomers ratio, dilution, and temperature), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In general, the silicon atom is part of a siloxane moiety, which implies a Si-O bond. [20][21][22][23][24][25] In 2014, Zaltariov et al 26 reported a PAM with a central silicon atom bonded to four carbon atoms complexed with different metal ions. However, they used a methylene unit instead of an aromatic moiety bonded to a silicon atom which, along with other structural features, rendered the polymer too exible; thus, the T g measured for the polymer was 48 C. For a material to be used for charge transport in a PHOLED device, its T g value must be over 100 C to avoid deterioration of its mechanical properties under high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the silicon atom is part of a siloxane moiety, which implies a Si-O bond. [20][21][22][23][24][25] In 2014, Zaltariov et al 26 reported a PAM with a central silicon atom bonded to four carbon atoms complexed with different metal ions. However, they used a methylene unit instead of an aromatic moiety bonded to a silicon atom which, along with other structural features, rendered the polymer too exible; thus, the T g measured for the polymer was 48 C. For a material to be used for charge transport in a PHOLED device, its T g value must be over 100 C to avoid deterioration of its mechanical properties under high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The A01-TPA was synthesized according to the previous work with modification 37 . TPA (14.7 g, 0.11 mol) was added to a 500 ml single-neck round flask and dissolve it with 200 ml of toluene, then A01 (50.1 g, 0.202 mol, 1 mol% excess to facilitate imine bond exchange) was added dropwise under stirring.…”
Section: Methodsmentioning
confidence: 99%